Challenges and opportunities affecting the success of e-government in Jordan: التحديات والفرص المؤثرة على نجاح الحكومة الالكترونية بالأردن - Duaa Ahmed Al-Hakban, Wiam Yahya Al Hayek (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2017)
The concept of e-government has recently emerged because of its application in many government agencies and ministries. In many countries, an important problem has emerged: the intellectual understanding of the concept of e-government by employees of government agencies and citizens, the non-issuance of legislation and laws regulating electronic transactions, e . The success of e-government programs varies greatly depending on the context being developed and implemented, and e-government implementation may face challenges in any country. Therefore, this study dealt with e-government one of the contemporary topics at the global level by identifying the challenges and opportunities that affect the success of e-government in the Hashemite Kingdom of Jordan. The study aimed to focus on the challenges facing the e-government in the Hashemite Kingdom of Jordan. On the success of e-government in Jordan. Scope of research: The research focuses on the intellectual understanding of the concept of e-government by employees of government agencies, ministries and citizens, and the non-issuance of legislation and laws governing electronic transactions and the absence of an electronic signature regulating electronic transactions in Jordan. Research Methodology and Research Tools: The descriptive descriptive approach was used, and the tools used in the research to collect resources are: books, research and literature, and the Internet. Research Sample: The research sample was selected from the selection of the experiences of some employees in the government agencies and ministries in the e-government in Jordan and were selected in a random stratified manner. Some of the results of the study: The reasons for the decline in government services and although the number is still a bit of electronic services developed, but the most important issue prevailing in the project is the lack of activation of a number of these services on the small number, as well as issues related to the program’s architecture and how to deal with data centers In various ministries, making many services so slow that beneficiaries do not want to use them because they are impractical.